Hematology Latest Research and Clinical Advances - Guenova, Margarita; Balatzenko, Gueorgui (IntechOpen, 2018)
Hematology has constantly been advancing in parallel with technological developments that have expanded our understanding of the phenotypic, genetic, and molecular complexity and extreme clinical and biological heterogeneity of blood diseases. This has in turn allowed for developing more effective and less toxic alternative therapeutic approaches directed against critical molecular pathways. The continuous and rather extensive influx of new information regarding the key features and underlying mechanisms as well as treatment options in hematology requires a frequent update of this topic. The primary objective of this book is to provide the specialists involved in the clinical management and experimental research in hematological diseases with comprehensive and concise information on some important theoretical and practical developments in the biology, clinical assessment, and treatment of patients, as well as on some molecular and pathogenetic mechanisms and the respective translation into novel therapies.